CHALLENGES AND POSSIBILITIES IN THE TRAINING OF ENGLISH LANGUAGE TEACHERS: A CASE STUDY OF THE PEDAGOGICAL RESIDENCY PROGRAM AT THE NORTH GOIANO STATE SCHOOL - Rapôso da Silva Ferreira, Gutemberg (Revista Gênero e Interdisciplinaridade, 2025)
This work investigates the challenges and opportunities in English language teacher training, focusing on the Pedagogical Residency Program at the North Goiano State School. The analysis reveals the relevance of integrating theory and practice, demonstrating how direct experience can amplify theoretical understanding. Critical literacy is highlighted as essential, pointing to the need for an approach that encompasses sociocultural and political issues in English learning. The role of the Residency Program is emphasized as instrumental in training critical and conscious educators, capable of teaching in a globalized context. The study concludes by highlighting the importance of constantly updating training programs and suggests future research to improve the effectiveness of initiatives such as the Pedagogical Residency, considering the contemporary demands of education.